2001
DOI: 10.1021/jm010127e
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Structure−Activity Relationships of Macrocyclic Hydroxamic Acids That Inhibit Tumor Necrosis Factor α Release in Vitro and in Vivo

Abstract: To search for TNF-alpha (tumor necrosis factor alpha) converting enzyme (TACE) inhibitors, we designed a new class of macrocyclic hydroxamic acids by linking the P1 and P2' residues of acyclic anti-succinate-based hydroxamic acids. A variety of residues including amide, carbamate, alkyl, sulfonamido, Boc-amino, and amino were found to be suitable P1-P2' linkers. With an N-methylamide at P3', the 13-16-membered macrocycles prepared exhibited low micromolar activities in the inhibition of TNF-alpha release from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 37 publications
1
53
0
Order By: Relevance
“…These macrocyclic compounds were developed by Bristol-Myers Squibb Medical Imaging on the basis of the previously reported structures of MMP inhibitors. 14 On the basis of the enzymatic assays performed previously and those described below, the structure of these MMP tracers bound specifically to MMPs and not other proteases. These compounds bind to the activated catalytic domain and therefore exhibit enzyme inhibitory profiles consistent with MMP inhibition.…”
Section: Mmp-targeted Radiotracersmentioning
confidence: 99%
See 1 more Smart Citation
“…These macrocyclic compounds were developed by Bristol-Myers Squibb Medical Imaging on the basis of the previously reported structures of MMP inhibitors. 14 On the basis of the enzymatic assays performed previously and those described below, the structure of these MMP tracers bound specifically to MMPs and not other proteases. These compounds bind to the activated catalytic domain and therefore exhibit enzyme inhibitory profiles consistent with MMP inhibition.…”
Section: Mmp-targeted Radiotracersmentioning
confidence: 99%
“…Therefore, the development of MMP-targeted tracers has been focused on constructs that will selectively bind to the active MMP catalytic domain. 14,[17][18][19][20] Chen et al 20 recently demonstrated the feasibility of ex vivo imaging of MMP activity after MI using a near-infrared fluorescent probe that is activated by the cleavage of 2 of the gelatinases (MMP2 and MMP9). However, application of MMP-targeted radiotracers or near-infrared fluorescent probes for in vivo myocardial imaging after an MI has not been performed previously.…”
Section: Role Of Mmp Activation In Post-mi Remodelingmentioning
confidence: 99%
“…With regard to DPPIV and autoimmunity, inhibition of DPPIV by Lys[ZNO2)]-pyrrolidide in murine experimental autoimmune encephalomyelitis (EAE) leads to decreased and delayed clinical and neuropathological signs of EAE possibly through a mechanism that includes an active TGF-bl-mediated anti-inflammatory effect at the site of pathology (Prud'homme and Piccirillo, 2000). In experimental rat and mouse models of colitis and arthritis, where TNF-a plays a role, the use of TACE inhibitors (BB1101 and GW3333) leads to a decrease of inflammation associated with the inhibition of TNF-a release (Colon et al, 2001;Conway et al, 2001;Newton et al, 2001;Xue et al, 2001;Doggrell, 2002). Two newly designed inhibitors of TACE (PKF242-484 and PKF-241-466) have beneficial effects in murine models of acute lung inflammation (asthma and chronic pulmonary disease) and other inflammatory diseases Trifilieff et al, 2002).…”
Section: Inhibition Of Tp Activity In Animal Modelsmentioning
confidence: 99%
“…5 To determine whether TACE inhibition would lead to alterations in LV structure in mice with targeted overexpression of wild-type, secretable TNF, 2 we used a hydroxamate TACE inhibitor, DPC-IDR1 (Bristol Myers Squibb). 13 For these studies, we used a previously reported line of transgenic mice with targeted cardiac overexpression of wild-type (secretable) murine TNF (referred to as MHCsTNF [C45BL6/ICR background]). 2 The MHCsTNF mice progress from a concentric hypertrophic phenotype to a dilated phenotype from 4 to 8 weeks of age.…”
Section: Tace Inhibitionmentioning
confidence: 99%